(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Traditional approaches do not ensure precise observation of the global maximum power point tracking (GMPPT) when there is partial shading (PS). Consequently, there is a notable decrease in the power output and the dependability of the PV energy generation system. For optimal solar panel performance under PS conditions, the GMPPT technique is necessary. An enhanced perturb and observe (P&O) method is presented in this work for tracking the GMPPT of solar arrays. The approach demonstrates superior performance, even in PS conditions, compared to traditional tracking methods. The initial detection of GMPP is achieved by modifying the command signal, after which the controller transitions to the local maximum power point level. The current work utilizes a single-ended primary inductance converter (SEPIC) as the direct current-direct current interface for MPPT. This is an optimized buck-boost derived converter specifically designed for photovoltaic (PV) applications, surpassing the capabilities of traditional buck-boost converters. An artificial solar photovoltaic (PV) panel has been simulated & PS impact have been incorporated. Presentation of simulation outcomes demonstrating the concert of the updated process using MATLAB/Simulink.